Allele diversity in cellulose synthase genes of the tropical pine species Pinus patula Schiede ex Schlect.&Cham - Myburg, Alexander Andrew (University of Pretoria, 2013)
Dissertation (MSc (Genetics))--University of Pretoria, 2009.